Haci Bektaş's Journey From Khorasan To Anatolia According To The Vilayetname - Doğan, Esra (Journal of Alevism-Bektashism Studies, 2011)
This research examines the journey of Hacı Bektaş Veli to Sulucakarahöyük according to the Vildyetndme (Hagiography) - It is con.fined to the voyage from Nishapur to Sulucakarahöyük, taking into account the cities he visited on his journey. Hacı Bektaş Veli travelled to Anatolia in a traditional manner following the caravan route of that era. Hence this work is the .first one to focus on this matter. The visited cities still exist to this day.
Keywords: Hacı Bektaş Veli; Khorasan; Vildyetndme; Nishabur; Sulucakarahöyük